Assessment of Produce Standardization Adopted by the Rice Farmers in the Marketing of their Rice Produce in Ebonyi State, Nigeria - Mgbanya, J.C; Eze, A. V; Obiora, C. C (Asian Journal of Agriculture and Rural Development, 2019)
The study assessed the produce standardization adopted by the rice farmers in the marketing of their rice produce in Ebonyi State, Nigeria. Multistage and random sampling techniques were employed in selecting 120 samples. Data were collected using structured questionnaire. Data obtained were analysed using descriptive statistics. The result obtained shows that the farmers sort and grade their produce according to: size (33.33%), anomalies (8.33%), shapes and appearance (25%). The result further showed that the packaging materials used by the farmers were: sack (100%), while the unit of measurement standard used by the farmer comprises of: unmeasured 50kg sack (95%) and unmeasured 100kg sack (88.33%). The result from the analysis of the social and economic effects of standard measures adopted by the farmer marketers include: misrepresentation of the product features and pricing (Xi = 4.52), misrepresentation of the quantity measurement (Xi = 4.05), etc. The ascertained constraints to rice produce standardization in Ebonyi state includes: lack of participation of Ebonyi state rice farmers in standard setting forums both at national and international level (Xi = 2.89). The study strongly recommends that the farmers should use weighing balance during marketing of their sorted and graded rice produce.